The prevalence and characteristics of frailty in cirrhosis patients: a meta-analysis and systematic review - Xie, Ruiyu; Jing, Xiaotong; Yang, Chuanjie (Frontiers in Medicine, 2024)
Objectives: This study aimed to assess the prevalence of frailty in cirrhosis patients and the distribution of age, sex, and body mass index (BMI) in cirrhotic patients with frailty. Methods: We performed a thorough literature search using PubMed, Embase, Web of Science, Cochrane Library from inception to February 29 2024. The estimated prevalence with 95% confidence interval (CI) was calculated with a random effect model. Subgroup analysis and sensitivity analysis were performed to assess the heterogeneity and characterize the distribution of age, sex, and body mass index (BMI) in cirrhotic patients. Publication bias was assessed by funnel plot, Begg’s test and Egger’s test. Results: The 16 included studies, which were all observational, reported a prevalence of frailty in 8406 cirrhosis patients ranging from 9% to 65%, and the overall estimated prevalence was 27% (95% CI: 21-33%; I2=97.7%, P<0.001). This meta-analysis indicated that the estimated prevalence of frailty in cirrhosis patients stayed at a high level, and comparing the non-frail cohort, the frail patients tended to have higher mean age and proportion of males which in the mean was 63.3 (95% CI: 59.9, 66.7; Z=36.48; P<0.001) and 73.5% (95% CI: 71.4, 75.5%; Z=7.65; P<0.001) with worse liver function in which 54.8% (95% CI: 43.1, 66.5%; P<0.001) and 23.4% (95% CI: 13.2, 33.7%; P<0.001) were classified into Child-Pugh B and C. Meanwhile, the patients in the non-frail cohort are more likely to have a higher BMI which in the mean was 28.4 (95% CI: 24.1, 32.7; Z=13.07; P<0.001). Conclusions: The current study suggests that cirrhosis patients have a high level of prevalence of frailty. Comparing with the non-frail cohort, the frail patients tend to be male, older, and have a lower BMI with worse liver function.